High-throughput identification of peptide agonists against GPCRs by co-culture of mammalian reporter cells and peptide-secreting yeast cells using droplet microfluidics - Kenshi Yaginuma (Nature Portfolio, 2019)
Abstract Since G-protein coupled receptors (GPCRs) are linked to various diseases, screening of functional ligands against GPCRs is vital for drug discovery. In the present study, we developed a high-throughput functional cell-based assay by combining human culture cells producing a GPCR, yeast cells secreting randomized peptide ligands, and a droplet microfluidic device. We constructed a reporter human cell line that emits fluorescence in response to the activation of human glucagon-like peptide-1 receptor (hGLP1R). We then constructed a yeast library secreting an agonist of hGLP1R or randomized peptide ligands. We demonstrated that high-throughput identification of functional ligands against hGLP1R could be performed by co-culturing the reporter cells and the yeast cells in droplets. We identified functional ligands, one of which had higher activity than that of an original sequence. The result suggests that our system could facilitate the discovery of functional peptide ligands of GPCRs.